2016
DOI: 10.1007/s00244-016-0303-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Residues Affecting the UNESCO Biosphere Reserve Kristianstads Vattenrike Wetlands: Sources and Sinks

Abstract: This study is the first to investigate the pharmaceutical burden from point sources affecting the UNESCO Biosphere Reserve Kristianstads Vattenrike, Sweden. The investigated Biosphere Reserve is a >1000 km2 wetland system with inflows from lakes, rivers, leachate from landfill, and wastewater-treatment plants (WWTPs). We analysed influent and treated wastewater, leachate water, lake, river, and wetland water alongside sediment for six model pharmaceuticals. The two WWTPs investigated released pharmaceutical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In Northeastern Scania, Kristianstad WWTP and Gärds Köpinge WWTP were both included. Both are situated in the UNESCO Biosphere Reserve Area Kristianstads Vattenrike [ 67 ] and connected to the basin of the Helge Å river, as described in more detail in our previous paper [ 68 ]. Kristianstad WWTP discharges wastewater into a 1500 m long canal, that ends in the Hammarsjön lake.…”
Section: Methodsmentioning
confidence: 99%
“…In Northeastern Scania, Kristianstad WWTP and Gärds Köpinge WWTP were both included. Both are situated in the UNESCO Biosphere Reserve Area Kristianstads Vattenrike [ 67 ] and connected to the basin of the Helge Å river, as described in more detail in our previous paper [ 68 ]. Kristianstad WWTP discharges wastewater into a 1500 m long canal, that ends in the Hammarsjön lake.…”
Section: Methodsmentioning
confidence: 99%
“…More than 1000 different active pharmaceuticals ingredients (APIs) are today used in Sweden [1]. The release of APIs into the water environment has been a subject of research for more than 30 years [2], and their ubiquitous occurrence at varying concentration levels have been shown in wastewater, surface water, sediment, groundwater and drinking water [3][4][5][6][7][8][9]. Large research resources have been spent worldwide on investigating the occurrence of pharmaceutical residues in the water phase, a significantly smaller proportion resources of these compounds' presence in sewage sludge [10].…”
Section: Introductionmentioning
confidence: 99%
“…In their pioneering work, performed on their in-house constructed equipment using stainless-steel columns, they found an increase in solubility of non-polar organics such as polyaromatic hydrocarbons (PAHs) in water with increasing temperature. The basic experimental set-up presented by Hawthorne and co-workers [24] has previously been used by us for the extraction of APIs from sediment [9], using a stainless-steel column Pressurized Hot Water Extraction system (PHWE method). This system and methodology was applied in this work as a reference methodology using a temperature of 150 • C as it has previously been shown that temperatures exceeding 100 • C has a very positive effect on extraction efficiency for pharmaceuticals in solid matrices [25].…”
Section: Introductionmentioning
confidence: 99%